Analisis Insentif Terhadap Kinerja Pegawai Tetap dan Pegawai Perjanjian Kurun Waktu Tertentu - Fendy Bayu Firmansyah; Nisa Mutiara (Universitas Islam Kadiri, 2023)
Competition between businesses that are increasingly intense, requires every company to be able to improve the quality of Human Resources (HR). Performance is still a concern for organizational and company stakeholders, because performance is the output displayed by each employee. One of the factors that affect the performance of an employee is the provision of incentives. The purpose of this study was to analyze the effect of providing incentives for jobholders on performance, to analyze the effect of providing incentives for PKWT employees on performance, and to analyze the effect of differences in the provision of incentives for permanent employees and PKWT. Data was collected through distributing questionnaires to employees of PT. Bukit Dhoho Indah Kediri, either directly or indirectly. The population used is 23 jobholders and 27 PKWT employees at PT. Bukit Dhoho Indah. The methods used to collect data are the documentation method and the questionnaire method. Data analysis in this study used simple regression analysis with the help of SPSS version 2.0. Testing of instrument data includes validity test, reliability test, F test and t test. The results of this study indicate that the provision of incentives has a significant effect on jobholders and PKWT employees, and the results of the t-test analysis show that PKWT employees have a value of 0.681 greater than jobholders with a t-test value of 0.478.